KUALITAS TELUR PUYUH (COTURNIX COTURNIX JAPONICA) YANG DIBERI PAKAN KOMERSIAL DENGAN PENAMBAHAN TEPUNG BAWANG PUTIH DANTEPUNG JINTAN - Fadila, Ulfa; Kardaya, Dede; Dihansih, Elis (Jurnal Peternakan Nusantara, 2019)
Research on the egg quality of quail (Coturnix coturnix japonica) fed garlic flour and cumin flour supplemented commercial has been done for one month to assess the effect of each treatment on the eggs quality of quail. This study used 180 quail aged 30 days with a complete randomized design study method treated as follows: P0 (commercial feeding without garlic flour and cumin flour, P1 (commercial feeding with 2% garlic flour), P2 ( Commercial feeding with 2% cumin flour), and P3 (1% garlic flour and 1% cumin flour). The addition of 1-2% garlic feed additive potency to improve the quality of quail eggs, especially on the quality of quail egg yolk. Key words : quality of quail eggs, garlic flour, cumin flour.